The Impact of Information Sharing on Competitive Strategies and the Performance of Supply Chain - حسین رحمان سرشت; امیر افسر (Journal of Information Technology Management)
The role of information sharing in achieving competitiveness has been the hub of attention of many recent researches at different level of company business and supply chain. In this research, the impact of information sharing on competitive strategies and the performance of supply chain is emphasized. To do so, regarding to competitive advantage of steel industry in Iran, the steel supply chain consists of the three companies of "Mobarakeh Steel", "Khuzestan Steel", and "Isfahan Steel" was selected and the opinion of 95 managers and experts of these companies were surveyed. Int the next stage, the structural equation modeling was used to analyze the data. The results indicate that there is a meaningful and positive relation between information sharing on competitive strategies of supply chain and also the same relationship between competitive strategies of supply chain and performance of supply chain.